Media Ecology and the Blurring of Public and Private Practices: A Case from the Middle East - de Franco, Chiara (Politik, 2016)
This paper aims at posing the basis for a new conceptualization of the impact of ‘old’ and ‘new’ media in international politics by creating a dialogue between the practice theoretical approach in IR (Adler and Pouliot 2011) and the medium theory in media studies (Meyrowitz 1985). Building on these approaches, the paper argues that in order to understand the role of the media in international politics it is necessary to shift the focus from media outlets and organisations to the media as environments, and from media content to media ecology. In fact, the paper argues that changes in the media ecology can produce changes in the social settings where international practices develop. It particular, it argues that the media ecology can affect the articulation of public and private and lead to the emergence of international practices where appropriate and competent behaviour reconstitute the private in the public (and vice versa). To explore its theoretical claims further and clarify how useful this approach can be to understand the role of the media in the Middle East, the paper discusses how an Israeli/Iranian movement catalysed by a Facebook (FB) page attempts at fostering peace. It explains how such a group has developed a Transnational Activist Network (TAN) bringing people together through shared private experiences.